Egy kultúra, két kultúra, sok kultúra: A kanadai konföderáció és a Charlottetowni Egyezség - T. Espák, Gabriella (Studia Litteraria, 2016)
On the occasion of the 150th anniversary of the Canadian Confederation, this paper surveys the various visions of society Canada has lived through until recently. Monocultural, bicultural, multicultural models of political identity alternated to clash over the constitution, thereby making it impossible for Aboriginal peoples and Québécois to deliver nationalist arguments through the wall of liberal egalitarianism. The failure of the Meech Lake Accord pushed the country towards a federal and identity crisis inasmuch as it failed to reconcile the interests of national minorities with the interest of the nation as a whole within one legal framework. Continuing clashes over the constitution in the Canada-round at Charlottetown 1991-92, culminating in a failed referendum on the proposed constitutional amendment known as the Charlottetown Accord, show that inherent cleavages in the body politic have survived, so multiculturalism has only been a partial solution to a population management problem.